A Convenient Way to Prepare the Key Intermediate 3-Aminomethyl-3-methyl-4-(metho-xyimino)pyrrolidine Dihydrochloride of DW286, a New Naphthyridone Antibacterial - Feng, Lian-Shun; Liu, Ming-Liang; Lv, Kai; Chai, Yun; Wang, Shuo; Cao, Jue; Guo, Hui-Yuan (Asian Journal of Chemistry, 2012)
We report herein a convenient way to prepare the key intermediate 3-aminomethyl-3-methyl-4-(methoxyimino)pyrrolidine dihydrochloride of DW286, a new fluoronaphthyridone antibacterial agent, via a 4-step sequence in an overall yield of 56 %. In this procedure, it was crucial that selective reduction of the cyano group of the cyano ketone (5) was done successfully using 5 % Pd/C as the catalytic hydrogenation.